MORAL IN PROFESSIONAL DEVELOPMENT OF MILITARY EDUCATORS USE OF INHERITANCE - Ismanov Komil Ismanovich (Western European Studies, 2023)
The article is devoted to the issues of using the national spiritual heritage in the process of advanced training of military teachers and the scientific analysis of views on the Motherland, patriotism and selflessness
Keywords: Military pedagogy; teacher; national spiritual heritage; Motherland